Appendix 5.10: William Saunders and Jane Ryan - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
The following are contracts signed by Ferdinand Marcos and Imelda Marcos with Swiss Credit Bank. They prove the Marcoses’ use of pseudonyms—William Saunders for Ferdinand, Jane Ryan for Imelda—for their Swiss bank accounts. Also of interest are two details. First, both contracts were executed in early 1968—within Marcos’s first term (also during the minority of their children). Second is the specification in both that communications be forwarded “in double envelope” to “Antonio Martinez, P.O. Box 4539, Manila.” When one looks up “Antonio Martinez” and “Ferdinand/Imelda Marcos” online, among the results that come up is an investigative piece (“The Marcoses Never Really Left Home,” by Raissa Robles, 1 October 2014) that discusses the acquittal of Imelda Marcos from the charge of violating the Anti-Graft and Corrupt Practices Act (see Marcos v. Sandiganbayan , G.R. No. 126995). Among the justices who voted for acquittal was Antonio M. Martinez. However, this may be a coincidence; nobody who has seen these documents and written about them appears to have tried to determine who Antonio Martinez is—if that is his real name.